Preclinical evaluation of targeted therapies in Sdhb-mutated tumors. Issue 6 (11th May 2022) - Moog, Sophie; Salgues, Betty; Braik-Djellas, Yasmine; Viel, Thomas; Balvay, Daniel; Autret, Gwennhael; Robidel, Estelle; Gimenez-Roqueplo, Anne-Paule; Tavitian, Bertrand; Lussey-Lepoutre, Charlotte; Favier, Judith
Abstract : Therapies for metastatic SDHB -dependent pheochromocytoma and paraganglioma (PPGL) are limited and poorly efficient. New targeted therapies and identification of early non-invasive biomarkers of response are thus urgently needed for these patients. We characterized an in vivo allograft model of spontaneously immortalized murine chromaffin cells (imCC) with inactivation of the Sdhb gene by dynamic contrast-enhanced MRI (DCE-MRI) and 18 FDG-PET. We evaluated the response to several therapies: IACS-010759 (mitochondrial respiratory chain complex I inhibitor), sunitinib (tyrosine kinase inhibitor with anti-angiogenic activity), talazoparib (poly ADP ribose polymerase (PARP) inhibitor) combined or not to temozolomide (alkylating agent), pharmacological inhibitors of HIF2a (PT2385 and PT2977 (belzutifan)) and molecular inactivation of HIF2a (imCC Sdhb −/− shHIF2a). Multimodal imaging was performed, including magnetic resonance spectroscopy ( 1 H-MRS) to monitor the level of succinate in vivo . The allografted model of Sdhb −/− imCC reflected SDHB-deficient tumors, with increased angiogenesis and a particular avidity for 18 FDG. After 14 days of treatment, IACS-010759, sunitinib and talazoparib at high doses allowed a significant reduction of the tumor volumes. In contrast to the tumor growth inhibition observed in Sdhb −/− shHIF2a imCC tumors, pharmacological inhibitors of HIF2a (PT2385 and belzutifan) showed no antitumor action in this model, alone or in combination with sunitinib. 1 H-MRS, but not DCE-MRI, enabled the monitoring response to sunitinib, which was the best treatment in this study, promoting a decrease in succinate levels detected in vivo . This study paves the way for new therapeutic options and reveals a potential new early biomarker of response to treatment in SDHB -dependent PPGL.